Working with the Australian cinema industry to understand the movie-going experience. Issue 2 (3rd May 2020) - Weaving, Simon; Hight, Craig; Nobes, Karen; Pasvolsky, Claire
ABSTRACT: Although box office receipts for the theatrical release of movies have remained consistently high over the past decade, this tends to mask a slow erosion in the frequency of movie-going among the Australia population. Australians, it appears, are gradually losing the habit of going to the movies. This decline sits in marked contrast to increasing numbers of audiences preferring to engage with cinematic content through VOD and other digital platforms. Our engagement with industry stakeholders highlights the concerns of the Australian distribution and exhibition sectors of the industry about competition from a range of competing leisure and entertainment opportunities for Australian consumers. In this paper we argue that it is vital for the local industry to revise its current model of movie-going audiences, in order to better understand what consumers think about the 'cinematic experience' and how they value this experience in relation to the variety of competition from other leisure and entertainment experiences. We outline the opportunities to draw from insights across multiple disciplinary fields, in particular to explore the implications of applying 'the customer journey' to understanding the variety of social and material factors which may be in play in informing the decision-making of movie-going audiences.